Quy trình hoạt động quản trị thương hiệu cho các trường đại học Việt Nam: nghiên cứu trường hợp các trường đại học tư thục tại Hà Nội - Hoàng , Thị Minh Huệ; Nguyễn , Thị Mỹ Lộc; Nguyễn , Trung Kiên; Nguyễn , Anh Tuấn; Trần , Thị Lụa (Tạp chí Giáo dục, 2023)
Growing competition highlights the need for universities to understand, promote influence and manage a clear brand position. Universities face distinct challenges related to the university’s brand structure, internal challenges, and different stakeholder needs, which in turn require a process of governance. Brand value is evident in private universities in Hanoi. The article uses a qualitative method with face-to-face and online interviews conducted from February to June 2022 to confirm the identified results of the previous research period. Initially, in-depth interviews with experts and leaders of private universities in Hanoi were conducted, which then expanded to managers and lecturers holding the position of head of department. The research results of this phase present the process and decisions for brand management activities in a university, including: (1) Identifying, establishing and positioning brand values; (2) Planning and implementing university brand marketing programs; (3) Improve competitiveness; (4) Brand policies; (5) Connecting and building brand values; (6) Guiding, monitoring and evaluating brand management decisions. However, case studies are needed, especially as brand approaches tested do not emphasize consistency and accuracy in identity definition. Only then, new studies can begin to provide insights into the usefulness of university brand management in the most general, unambiguous sense.